Honoring Preferences—The Consistency Between End-of-Life Care and a Veteran's Goal for Comfort Care. (16th December 2020) - Carpenter, Joan; Scott, Winifred; Ersek, Mary; Levy, Cari; Cohen, Jennifer; Foglia, Mary Beth; Phibbs, Ciarian; Miller, Susan
Abstract: This study examined the alignment between Veterans' end-of-life care and a Life-Sustaining Treatment (LST) goal "to be comfortable." It includes Veterans with VA inpatient or community living center stays overlapping July 2018--January 2019, with a LST template documented by January 31, 2019, and who died by April 30, 2019 (N = 18, 163). Using VA and Medicare data, we found 80% of decedents with a comfort care goal received hospice and 57% a palliative care consult (compared to 57% and 46%, respectively, of decedents without a comfort care goal). Using multivariate logistic regression, a comfort care goal was associated with significantly lower odds of EOL hospital or ICU use. In the last 30 days of life, Veterans with a comfort care goal had 43% lower odds (AOR 0.57; 95% CI: 0.51, 0.64) of hospitalization and 46% lower odds of ICU use (AOR 0.54; 95% CI: 0.48, 0.61).